Impact of malnutrition on health-related quality of life in persons receiving dialysis: a prospective study. Issue 11 (14th June 2022) - Viramontes-Hörner, Daniela; Pittman, Zoe; Selby, Nicholas M.; Taal, Maarten W.
Abstract: Health-related quality of life (HRQoL) is severely impaired in persons receiving dialysis. Malnutrition has been associated with some measures of poor HRQoL in cross-sectional analyses in dialysis populations, but no studies have assessed the impact of malnutrition and dietary intake on change in multiple measures of HRQoL over time. We investigated the most important determinants of poor HRQoL and the predictors of change in HRQoL over time using several measures of HRQoL. We enrolled 119 haemodialysis and thirty-one peritoneal dialysis patients in this prospective study. Nutritional assessments (Subjective Global Assessment (SGA), anthropometry and 24-h dietary recalls) and HRQoL questionnaires (Short Form-36 (SF-36) mental (MCS) and physical component scores (PCS) and European QoL-5 Dimensions (EQ5D) health state (HSS) and visual analogue scores (VAS)) were performed at baseline, 6 and 12 months. Mean age was 64 (14) years. Malnutrition was present in 37 % of the population. At baseline, malnutrition assessed by SGA was the only factor independently (and negatively) associated with all four measures of HRQoL. No single factor was independently associated with decrease in all measures of HRQoL over 1 year. However, prevalence/development of malnutrition over 1 year was an independent predictor of 1-year decrease in EQ5D HSS, and 1-year decrease in fat intake independently predicted the 1-year decline in SF-36 MCS and PCS, and EQ5D VAS. These findings strengthen the importance of monitoring for malnutrition and providing nutritional advice to all persons on dialysis. Future studies are needed to evaluate the impact of nutritional interventions on HRQoL and other long-term outcomes.